2018
DOI: 10.1111/jcmm.13726
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA NNTAS1 sponges miR‐424/E2F1 to promote the tumorigenesis and cell cycle progression of gastric cancer

Abstract: Long non‐coding RNAs (lncRNAs) have been illustrated to function as important regulators in carcinogenesis and cancer progression. However, the roles of lncRNA NNT‐AS1 in gastric cancer remain unclear. In the present study, we investigate the biological role of NNT‐AS1 in gastric cancer tumorigenesis. Results revealed that NNT‐AS1 expression level was significantly up‐regulated in GC tissue and cell lines compared with adjacent normal tissue and normal cell lines. The ectopic overexpression of NNT‐AS1 indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 29 publications
0
39
0
1
Order By: Relevance
“…In Erα-receptor-positive breast cancer cells, when E2 is monitored or E2 is given, the levels of miR-424 and E2F1 also increase [41,42]. In a gastric cancer study, the regulatory axis of NNT-AS1/miR-424/E2F1 was confirmed [32]. Therefore, the low expression of NNT-AS1 up-regulates miR-424 and E2F1, and the abnormal E2 level is likely to be correlated.…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 93%
See 1 more Smart Citation
“…In Erα-receptor-positive breast cancer cells, when E2 is monitored or E2 is given, the levels of miR-424 and E2F1 also increase [41,42]. In a gastric cancer study, the regulatory axis of NNT-AS1/miR-424/E2F1 was confirmed [32]. Therefore, the low expression of NNT-AS1 up-regulates miR-424 and E2F1, and the abnormal E2 level is likely to be correlated.…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 93%
“…However, studies on the expression of NNT-AS1 in gastric, breast, and ovarian cancers seem to be contradictory. In gastric cancer, there have been three studies that have reported high levels of NNT-AS1 in tumor tissues and cell samples, and the performance of NNT-AS1 in subsequent in vivo and in vitro tests also verified its cancer-promoting function [32,33,35]. However, Farbod Esfandi et al found that compared with the adjacent samples, the NNT-AS1 levels detected in gastric cancer samples were overall down-regulated [34].…”
Section: The Aberrant Expression Of Nnt-as1 In Cancermentioning
confidence: 99%
“…Recently, emerging studies have explored the possible link between expression of lncRNA NNT-AS1 and human tumors. Compared with adjacent noncancerous tissue and normal cell, upregulated NNT-AS1 expression was identi ed in most cancer tissues or cell lines and therefore indicated poor survival outcome, such as osteosarcoma [27], breast cancer [19], cervical cancer [26], gastric cancer [28], hepatocellular carcinoma [18], colorectal cancer [21], and non-small cell lung cancer (NSCLC) [2]. On the contrary, another study performed by Huang et al, claimed that NNT-AS1 was markedly downregulated in patients with ovarian cancer and ovarian cell lines [29].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, other pathways including PI3K/Akt/mTOR and Wnt/β-catenin signaling pathway were also found involved in the tumorigenesis and progression [26,15]. Besides, NNT-AS1 was capable of serving as a competing endogenous RNA (ceRNA) by sponging miR-485/BCL9 or miR-203 in cholangiocarcinoma [31,32], miR-1301-3p/PODXL or miR-496/HMGB1 in bladder cancer [3,33], miR-142-3p/ZEB1 in breast cancer [19], miR-424/E2F1 or miR-363 in gastric cancer [28,8], miR-22-3p/YAP1 or miR-129-5p in non-small cell lung cancer [34,30], and miR-320a in osteosarcoma [27], therefore alteration in cancer cell function resulting from NNT-AS1 downregulation may be rescued by miRNA inhibition. Notably, NNT-AS1 also showed a high expression level in drug-resistant NSCLC, which promoted the cisplatin resistance of cancer cells via the MAPK/Slug pathway [35].…”
Section: Discussionmentioning
confidence: 99%
“…84 With regards to the digestive system, Lnc-RNA NNT-AS1 can affect the tumorigenesis and cell cycle of gastric cancer cells by binding to miR-424/E2F1. 88 Moreover, in hepatocellular carcinoma, LncRNA-LINC00511 plays an important role in the malignant progression of HCC by regulating miR-424. 89 Another study has found that Lnc-RNA DLX6-AS1 increases the expression of WEE1 by targeting miR-424-5p, which in turn promotes hepatocellular carcinoma.…”
Section: Molecules That Regulate the Expression Of Mir-424 In Tumors mentioning
confidence: 99%